Frank J. Cannon : Saint, Senator, Scoundrel - Holley, Val (Book collections on Project MUSE., 2020)
"Frank J. Cannon: Saint, Senator, Scoundrel is the first biography to refresh the record on Frank J. Cannon's critical role in early Utah history"--